Reactivity and reactions to regulatory transparency in medicine, psychotherapy and counselling - McGivern, G; Fischer, M (Elsevier, 2012)
We explore how doctors, psychotherapists and counsellors in the UK react to regulatory transparency, drawing on qualitative research involving 51 semi-structured interviews conducted during 2008-10. We use the concept of ‘reactivity mechanisms’ (Espeland and Sauder, 2007) to explain how regulatory transparency disrupts practices through simplifying and decontextualizing them, altering practitioners’ reflexivity, leading to defensive forms of practice. We make an empirical contribution by exploring the impact of transparency on doctors compared with psychotherapists and counsellors, who represent an extreme case due to their uniquely complex practice, which is particularly affected by this form of regulation. We make a contribution to knowledge by developing a model of reactivity mechanisms which explains how clinical professionals make sense of media and professional narratives about regulation in ways that produce emotional reactions and, in turn, defensive reactivity to transparency.